PRODUKSI RUMPUT (Pennisetum purpureum cv. Mott) DEFOLIASI I PERTAMA DENGAN JENIS PUPUK YANG BERBEDA - Dylla Pramanti rukaman Dewi (AVES: Jurnal Ilmu Peternakan, 2017)
The aims of the study is to determine the effect different fertilizer types on Pennisetum purpureum cv. Mott grass production. A randomized completely design was applied with 4 treatment and 16 replication. The treatment consist of P0 - control (using basic fertilizer SP -“ 36), P1= basic fertilizer and 765 kg per hectare of organic fertilizer, P2= basic fertilizer and 250 kg per hectare of urea fertilizer, P3= basic fertilizer and 720 kg per hectare of N -“ P - K fertilizer. Observed variables include leaf colour indeks, fresh weight, dry weight productions, higher plants, number of chicks, stem circumference, hill circumference, leaf length, leaf width, and number of leaf. The conclusion based on the result were the treatment not significant ( P > 0, 05) on all variabel because due to the equalization of the nitrogen element given to the plant. It ’s suggested to use manure for more efficient production.Keyword: Pennisetum purpureum cv. Mott, fertilizer, nitrogen